A web-based listening methodology for studying relative clause acquisition - Romeo, Kenneth (Computer assisted language learning, 2008)
This paper addresses the comprehension of relative clauses in audio prompts using online listening exercises implemented in a classroom. Reaction time to short and long sentences containing subject and object relative clauses was assessed in subjects attending an intensive ESL course for graduate students. The results indicate the possibility that learners shift resources when processing more syntactically complex audio prompts, such as those with object relatives. This shift from a discrete measure such as accuracy to a continuous variable like reaction time accommodates theoretical frameworks which do not rely on categorical paradigms of learning.